2011
DOI: 10.2147/copd.s14247
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of fluticasone propionate/salmeterol fixed-dose combination and incidence of cataracts and glaucoma among chronic obstructive pulmonary disease patients in the UK General Practice Research Database

Abstract: ObjectivesSome large population-based studies have reported a dose-related increased risk of cataracts and glaucoma associated with use of inhaled corticosteroids (ICS) in patients with asthma or chronic obstructive pulmonary disease (COPD). We evaluated the association between use of ICS-containing products, specifically fluticasone propionate/salmeterol fixed-dose combination (FSC), and incidence of cataracts and glaucoma among patients with COPD in a large electronic medical record database in the United Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(23 reference statements)
0
14
1
1
Order By: Relevance
“…Indeed, a constant oxygen supply is crucial for adequate organ function 44 ., andeven small changes in oxygen supply to the retina can result in tissue hypoxia and retinal changes 44 . In addition, exposure to corticosteroids may contribute to an increased risk of glaucoma and cataract, though results in patients with COPD are contradictory [45][46][47] . An earlier review demonstrated that structural and functional changes in the retinal microvasculature are more common and severe in patients with COPD compared to non-COPD controls, including increased retinal vessel diameter, lower retinal arterial oxygen saturation, impaired haemodynamics and increased resistive index of the orbital vessels 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a constant oxygen supply is crucial for adequate organ function 44 ., andeven small changes in oxygen supply to the retina can result in tissue hypoxia and retinal changes 44 . In addition, exposure to corticosteroids may contribute to an increased risk of glaucoma and cataract, though results in patients with COPD are contradictory [45][46][47] . An earlier review demonstrated that structural and functional changes in the retinal microvasculature are more common and severe in patients with COPD compared to non-COPD controls, including increased retinal vessel diameter, lower retinal arterial oxygen saturation, impaired haemodynamics and increased resistive index of the orbital vessels 43 .…”
Section: Discussionmentioning
confidence: 99%
“…GCs improve symptoms of active RA through reducing joint pain, swelling and stiffness [ 6 ]. However, there are some concerns about their potential side effects including cardiovascular (CV) events, diabetes, infection, fracture, and cataracts [ 7 11 ], many of which are associated with an increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, cataract and glaucoma have been studied in CPRD in association with various drugs. [7][8][9][10][11][12][13][14][15][16] Two previous studies validated ICD codes for cataract diagnoses with high validity (94% and 97%). 14,15 Glaucoma was also validated by one study, which confirmed 89% of the cases.…”
Section: Introductionmentioning
confidence: 99%